2015
DOI: 10.1039/c4pp00309h
|View full text |Cite
|
Sign up to set email alerts
|

A novel set of symmetric methylene blue derivatives exhibits effective bacteria photokilling — a structure — response study

Abstract: This study focuses on the structure-response relationship of symmetrically substituted phenothiazinium dyes. Four hydrophilic derivatives with the ability of additional hydrogen bonding (, ) or additional electrostatic interaction (, ) were synthesized, photophysically characterized and compared to the parent compound methylene blue (MB, ) and a lipophilic derivative () without additional coordination sites. Derivative was most effective against Gram-positive Staphylococcus aureus and Gram-negative Escherichia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 58 publications
(119 reference statements)
2
23
0
Order By: Relevance
“…Methylene blue derivatives (structures are summarized in Table 2) such as new methylene blue, dimethyl methylene blue, and methylene green were developed with different functional substituents and shown to have improved effectiveness of killing bacteria. As indicated previously, increasing the positive charge on methylene blue correlated positively with increased APDT efficacy than native methylene blue [19,20], mainly because substitution with cationic functional groups improved the binding and uptake of the PS by bacteria relative to the parent structure [19][20][21]. For example, Felgentrager et al revealed that derivatization of methylene blue with tertiary ammonium substituents increased the uptake by microbial cells due to the fact that these substituents imposed a greater cationic charge in a pH-equilibrated aqueous solution, and therefore more avid bacterial cell binding, compared to primary or secondary substituents [19].…”
Section: Phenothiaziniumssupporting
confidence: 71%
“…Methylene blue derivatives (structures are summarized in Table 2) such as new methylene blue, dimethyl methylene blue, and methylene green were developed with different functional substituents and shown to have improved effectiveness of killing bacteria. As indicated previously, increasing the positive charge on methylene blue correlated positively with increased APDT efficacy than native methylene blue [19,20], mainly because substitution with cationic functional groups improved the binding and uptake of the PS by bacteria relative to the parent structure [19][20][21]. For example, Felgentrager et al revealed that derivatization of methylene blue with tertiary ammonium substituents increased the uptake by microbial cells due to the fact that these substituents imposed a greater cationic charge in a pH-equilibrated aqueous solution, and therefore more avid bacterial cell binding, compared to primary or secondary substituents [19].…”
Section: Phenothiaziniumssupporting
confidence: 71%
“…In 2015, they further observed that increasing polarity of these MB derivatives through the ammonium groups would promote better uptake by the bacteria. A maximum photodynamic efficacy of > 5log 10 steps (99.999%) against S. aureus and E. coli has been reached in 10 minutes at 5 μM concentration . Phenothiazines are increasing utilized in PDI due to their absorption band between 600 and 800 nm.…”
Section: Photosensitizers In Photodynamic Inhibitionmentioning
confidence: 99%
“…A maximum photodynamic efficacy of > 5log 10 steps (99.999%) against S. aureus and E. coli has been reached in 10 minutes at 5 µM concentration. [ 88 ] Phenothiazines are increasing utilized in PDI due to their absorption band between 600 and 800 nm. The disadvantage of phenothiazine dyes is their inherent toxicity, which reduces their therapeutic effectiveness.…”
Section: Phenothiazinium Chromophorementioning
confidence: 99%
“…The authors stated better polarity characteristics of these MB derivatives by the use of these functional groups facilitating a better attachment of even uptake by the bacteria. In another study additional positive charges or hydrogen bond acceptors on symmetrically substituted phenothiazinium molecules were investigated [42]. The focus in this study was that positive charges were added on both sides of the core group of methylene blue.…”
Section: Phenothiazinium Chromophorementioning
confidence: 99%